2005
DOI: 10.1038/sj.gt.3302585
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Progress and Prospects: Viral trafficking during infection

Abstract: The intracellular steps involved in viral infection, namely cytoplasmic trafficking and nuclear import, are critical events in the viral life cycle that have lagged behind other areas of viral research. This review examines recent advances in our understanding of these steps for viruses commonly employed as viral gene delivery vectors. Steps governing the cytoplasmic trafficking and nuclear import of Herpes Simplex virus, Human Immunodeficiency virus and Adenovirus are reviewed in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Disruption of the inner limiting membrane caused by mild proteolytic digestion, 72 by structural changes of the Müller cell endfeet, 73 by laser pretreatment, 74 or by retinal degeneration 72 allow for enhanced AAV transduction of outer retinal cells after their intravitreal delivery. Moreover, nuclear uptake, capsid uncoating, and second-strand DNA synthesis following receptor binding are major rate-limiting steps in AAV transduction [75][76][77][78] that need to be investigated.…”
Section: Aav2 Vectors Reverse Diabetic Retinal Alterations N Díaz-lezmentioning
confidence: 99%
“…Disruption of the inner limiting membrane caused by mild proteolytic digestion, 72 by structural changes of the Müller cell endfeet, 73 by laser pretreatment, 74 or by retinal degeneration 72 allow for enhanced AAV transduction of outer retinal cells after their intravitreal delivery. Moreover, nuclear uptake, capsid uncoating, and second-strand DNA synthesis following receptor binding are major rate-limiting steps in AAV transduction [75][76][77][78] that need to be investigated.…”
Section: Aav2 Vectors Reverse Diabetic Retinal Alterations N Díaz-lezmentioning
confidence: 99%
“…Some studies in this area have also suggested that the rate of intracellular processing and the process of uncoating of viral vectors may critically affect host immune responses toward input capsids, in the absence of new viral protein synthesis (Campbell and Hope, 2005;Ding et al, 2005).…”
Section: Adeno-associated Virus Biology and Trafficking In Host Cellsmentioning
confidence: 99%
“…The knowledge of the intracellular processing in these and other existing serotypes is becoming even more important with the increasing identification of new AAV serotypes (Campbell and Hope, 2005;Ding et al, 2005).…”
Section: Adeno-associated Virus Biology and Trafficking In Host Cellsmentioning
confidence: 99%
“…HIV-1 has been shown to use actin microfilaments for short-range transport at the cell and nuclear periphery, and MT motors for long-range intracellular movement (10,75,76). Confusingly, numerous non-motile tubulin-and actin-associated proteins have been identified by genomewide screens of proteins thought to contribute to efficient HIV-1 infection (77-79).…”
Section: Maps Facilitate Interaction Of Viruses With Microtubulesmentioning
confidence: 99%